AH-11 Expression of N-Acetylglucosamine Residues in Abomasum of The Swamp Buffalo - Anni Nurliani; Teguh Budipitojo; Dwi Liliek Kusindarta (Media Veteriner, 2015)
Expression of N-Acetylglucosamine Residues in Abomasum of The Swamp Buffalo